Recent Advances in Hollow Porous Carbon Materials for Lithium–Sulfur Batteries. Issue 10 (5th February 2019) - Fu, Ang; Wang, Chaozhi; Pei, Fei; Cui, Jingqin; Fang, Xiaoliang; Zheng, Nanfeng
Abstract: Lithium–sulfur (Li–S) batteries are considered as one of the most potential next‐generation rechargeable batteries due to their high theoretical energy density. However, some critical issues, such as low capacity, poor cycling stability, and safety concerns, must be solved before Li–S batteries can be used practically. During the past decade, tremendous efforts have been devoted to the design and synthesis of electrode materials. Benefiting from their tunable structural parameters, hollow porous carbon materials (HPCM) remarkably enhance the performances of both sulfur cathodes and lithium anodes, promoting the development of high‐performance Li–S batteries. Here, together with the templated synthesis of HPCM, recent progresses of Li–S batteries based on HPCM are reviewed. Several important issues in Li–S batteries, including sulfur loading, polysulfide entrapping, and Li metal protection, are discussed, followed by a summary on recent research on HPCM‐based sulfur cathodes, modified separators, and lithium anodes. After the discussion on emerging technical obstacles toward high‐energy Li–S batteries, prospects for the future directions of HPCM research in the field of Li–S batteries are also proposed. Abstract : Hollow porous carbon materials (HPCM) are one class of promising functional materials to improve the performance of lithium–sulfur batteries. The recent advances in the hard‐templating synthesis of HPCM and the HPCM‐based sulfur cathodes, modified separators, and Li metal anodes, which are helpful for the development of lithium–sulfur batteries, are summarized.